2010
DOI: 10.1002/eji.201040523
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells adhere to and transmigrate across lymphatic endothelium in response to IFN‐α

Abstract: Migration of DC into lymphatic vessels ferries antigenic cargo and pro-inflammatory stimuli into the draining LN. Given that tissues under the influence of viral infections produce type I IFN, it is conceivable that these cytokines enhance DC migration in order to facilitate an antiviral immune response. Cultured lymphatic endothelium monolayers pretreated with TNF-a were used to model this phenomenon under inflammatory conditions. DC differentiated in the presence of either IFN-a2b or IFN-a5 showed enhanced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 56 publications
(77 reference statements)
0
50
0
Order By: Relevance
“…In fact, we and others have demonstrated that integrin ligands are induced on lymphatic endothelial cells under inflammation. Indeed, the inhibition of integrin ligands in mice significantly reduced the number of exogenously injected DCs that reached the lymph nodes under inflammation (Johnson and Jackson, 2008;Podgrabinska et al, 2009;Rouzaut et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, we and others have demonstrated that integrin ligands are induced on lymphatic endothelial cells under inflammation. Indeed, the inhibition of integrin ligands in mice significantly reduced the number of exogenously injected DCs that reached the lymph nodes under inflammation (Johnson and Jackson, 2008;Podgrabinska et al, 2009;Rouzaut et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have demonstrated the upregulation of adhesive molecules such as E-selectin and the integrin ligands ICAMs and vascular cell adhesion molecule-1 (VCAM) on lymphatic endothelial cells (LECs) under inflammation Jackson, 2010, Vigl et al, 2011). Furthermore, we and others have demonstrated how b2 and b1 integrin blockade decreases DC migration to the lymph nodes under inflammatory conditions (Podgrabinska et al, 2009, Rouzaut et al, 2010, Nitschké et al, 2012. Interestingly, active epitopes of aLb1 (LFA-1) integrin are induced in human dendritic cells after exposure to chemokines such as CCL21 (Eich et al, 2011), produced by lymphatic endothelial cells.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, experiments in mice have also shown that IFN-a/b is required for plasmacytoid DCs (pDC) to migrate from the marginal zone into the T-cell area, where they form clusters (49). We have also recently shown that IFNs-I enhance the adhesion and extravasations of DCs across inflamed lymphatic endothelium in a lymphocyte function-associated antigen 1 (LFA-1)-and very late antigen-4 (VLA4)-dependent fashion (50). IFNs-I may also favor the encounter between DCs and specific lymphocytes in lymph nodes by promoting lymphocyte trapping in lymph nodes upon downmodulation of sphingosine 1-phosphate (51).…”
Section: Effects Of Ifns-i On Cells Of the Immune Systemmentioning
confidence: 99%
“…These studies and others indicate that LECs are capable of expressing and actively signaling through a variety of cytokines and adhesion receptor-ligand interactions important in immunity (Tables 1, 2, and 3, and refs. 17,[27][28][29][30].…”
Section: Figurementioning
confidence: 99%